2017
DOI: 10.1037/neu0000326
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in college students with and without ADHD.

Abstract: Increasing numbers of students with attention-deficit/hyperactivity disorder (ADHD) are attending college; however, little empirical information is available concerning the functional impairment experienced by these students. Although preliminary studies suggest that college students with ADHD are more likely to experience a variety of psychosocial and academic difficulties compared to their peers without the disorder, findings regarding neuropsychological functioning have been inconsistent with some studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 85 publications
3
58
0
3
Order By: Relevance
“…Moreover, we identified that many participants endorsing marijuana use reported doing so because they thought it would make their ADHD symptoms better or help with medication side effects; this is very concerning given that adolescent marijuana use can result in impairments in executive functioning, a source of the symptomatology in ADHD, 16 and cognitive skills later in adulthood. 17, 18 Although older participants were more likely to know that alcohol can interfere with medications, they were not more likely to know that alcohol can make ADHD symptoms worse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we identified that many participants endorsing marijuana use reported doing so because they thought it would make their ADHD symptoms better or help with medication side effects; this is very concerning given that adolescent marijuana use can result in impairments in executive functioning, a source of the symptomatology in ADHD, 16 and cognitive skills later in adulthood. 17, 18 Although older participants were more likely to know that alcohol can interfere with medications, they were not more likely to know that alcohol can make ADHD symptoms worse.…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacotherapy is the most prevalent treatment for ADHD in adults (Danielson, Visser, Chronis‐Tuscano, & DuPaul, ) with demonstrated benefits in the college population (DuPaul et al, ), studies of college students with ADHD generally have not found an association between medication treatment and improved academic functioning (Advokat et al, ; Blase et al, ; Rabiner et al, ) or increased study time (Advokat et al, ). Additional study is needed to replicate those findings and to determine why medication‐enhanced vigilance and impulse control (Weyandt et al, ) have not been found to translate into improved academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Third, some evidence has suggested that comorbid psychiatric disorders result in executive dysfunction beyond what is expected for either ADHD or a psychiatric diagnosis alone (Weyandt et al, ). Consistent with previous findings for college ADHD (Anastopoulos et al, ), 30% of the ADHD sample in the current study had comorbid diagnoses of depression and/or anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Attention‐deficit hyperactivity disorder (ADHD) is characterized by clinically significant symptoms of hyperactivity, impulsivity, and/or inattention and occurs in approximately 2.5% of the adult population . Generally, adults with ADHD are at greater risk for comorbid psychiatric diagnoses and have demonstrated executive function impairments compared to adults without ADHD . Although females are diagnosed with ADHD less frequently than males, preliminary evidence suggests women may be more likely than men to continue to experience ADHD symptoms as adults .…”
Section: Introductionmentioning
confidence: 99%
“…1 Generally, adults with ADHD are at greater risk for comorbid psychiatric diagnoses 2 and have demonstrated executive function impairments compared to adults without ADHD. 3 Although females are diagnosed with ADHD less frequently than males, 1,4 preliminary evidence suggests women may be more likely than men to continue to experience ADHD symptoms as adults. 5 Indeed, the use of pharmacologic therapies for ADHD during pregnancy has steadily increased over the past decade.…”
Section: Introductionmentioning
confidence: 99%